Gene vaccines - Weiss, Richard; Scheiblhofer, Sandra; Thalhamer, Josef (Springer Vienna, 2012)
The induction of antigen-specific immune responses after in vivo transfection with expression plasmids has triggered a revolution of vaccine research. After a first hype, evoked by the fascinating options of this method, clinical studies did not reach the ambitious aims and a phase of disillusion ensued. It became obvious that Gene vaccines displayed a weaker immunogenicity in humans than had been observed in the mouse models. Meanwhile these hurdles have been overcome and gene vaccines undergo a renaissance. The present book gives an update of the "world of naked gene vaccines", namely DNA and RNA vaccines. Its content ranges from general mechanisms, inherent immunostimulatory properties and the vast potential to modulate immune responses, to recent successful clinical studies and approved veterinary gene vaccines. Beyond the state-of-the-art of genetic immunization, the reader will be stimulated with a chapter addressing "burning questions".